Highly Sensitive Hydrogen Gas Sensors Based on Gold Nanoparticle Decorated Zinc Oxide Nanosheets - Thierry Maffeis (Procedia Engineering, 2016)
Highly sensitive gold nanoparticle decorated zinc oxide nanosheet gas sensors have been fabricated using simple and rapid chemical methods capable of producing a normalised current gain of 2.54 (at 10V) in dry air containing 2.5ppm of hydrogen gas at 200C and a current gain of 382.53 under 125ppm. Compared to undecorated sheet based sensors where a response of 1.24 was observed under 125ppm at 200C a massive relative increase in signal is observed. The zinc oxide nanosheets are produced via a previously reported simple microwave assisted hydrothermal growth method and gold nanoparticles with mean diameter of 5nm synthesized via a simple sodium borohydride reduction of hydrogen tetrachloroaurate in the presence of polyvinylpyrrolidone (PVP) followed by drop casting onto a pre-patterned aluminium oxide substrate.